Stock Markets, Banks, and Growth : Correlation or Causality? - Beck, Thorsten; Levine, Ross (World Bank, Washington, DC, 2014)
The authors investigate the impact of stock markets and banks on economic growth using a panel data set for 1976-98 and applying recent generalized method of moments (GMM) techniques developed for dynamic panels. The authors illustrate econometrically the differences that emerge from different panel procedures. On balance, stock markets and banks positively influence economic growth--and these findings are not a result of biases induced by simulaneity, omitted variables, or inobserved country-specific effects.